Shifting Tax Burdens through Exemptions and Evasion : An Empirical Investigation of Uganda - Gauthier, Bernard; Reinikka, Ritva (World Bank, Washington, DC, 2014)
The authors look at how prevalent tax exemptions, and evasion are among businesses in Uganda, how they translate into actual tax burdens for firms of different sizes, and how the tax administration attempts to ensure compliance. Despite tax reforms undertaken in 1995-97 to increase the efficiency, and equity of the tax system, and its administration, exemptions, and evasion during this three-year period remained widespread, and the dispersion of the tax burden did not decrease. The analysis shows that tax evasion is more prevalent among smaller firms, that tax exemptions are more common among larger firms, and that medium-size firms tend to shoulder a disproportionate share of the total tax burden.